Referral patterns after a seizure admission in an English region: an opportunity for effective intervention? An observational study of routine hospital data. Issue 1 (20th January 2016) - Grainger, Ruth; Pearson, Michael; Dixon, Peter; Devonport, Elizabeth; Timoney, Michelle; Bodger, Keith; Kirkham, Jamie; Marson, Anthony
Abstract : Objectives: To identify emergency seizure admissions to hospital and their subsequent access to specialist outpatient services. Design: Algorithmic analysis of anonymised routine hospital data over 7 years using specialist follow-up by 3 months as the target outcome. Population: All adults resident in Merseyside and Cheshire, England. Main Outcomes: Whether, and when, access to the specialist advice that might prevent further admissions was offered. Results: 1.4% of all emergency medical admissions are as a result of seizure. In the following 12 months 35% were readmitted and experienced a mean of 2.3 emergency department visits. Only 27% (48% of those already known to specialists and 13% of those not known) were offered appointments. Subsequent attendance at a specialist clinic is more likely if already known to a clinic, if aged <35 years, if female, or required a longer spell in hospital. Extrapolation from other work suggests 100 000 bed days per annum could be saved. Conclusions: Most seizure admissions are not being referred for the help that could prevent future admissions. The majority of those that are referred are not seen within an appropriate time frame. Our service structures are not providing an optimum service for people with epilepsy.